Industrial agglomerations and wage gradients: the Spanish economy in the interwar period - Daniel A. Tirado; Jordi Pons; Elisenda Paluzie (European Regional Science Association (ERSA), 2003)
The geographical distribution of Spanish industry shows today two interesting features. On the one hand, a high concentration, higher than what we can find in the majority of European countries. On the other hand, the coexistence of two industrial cities: Madrid and Barcelona. In Spain, the larger increases in the levels of concentration are to be found during the long period that goes from the middle of the 19th century to the Civil War (1936-1939). As for the geographical location of large industrial centers, the second half of the 19th century was dominated by the rising of Barcelona as the main center of industrial production in Spain. In those years, Barcelona got to concentrate a third of Spanish industrial output. However, the turning of the century marks a halt in this process, and Madrid begins then to increase its share in Spanish manufacturing, filling the gap gradually with the Catalan city. In this paper we suggest two explanatory hypothesis to these facts. On the one hand, we believe that the increase in the geographical concentration of Spanish industries along the period 1850-1935 is linked to the existence of scale economies in a context of increasing domestic market integration. On the other hand, we think that the initial development of Barcelona as the Spanish industrial capital and its subsequent loss of punch in front of other locations like Madrid, both the capital-city of the country and its geographical center, could be related, though not exclusively, with the changes in Spanish trade policy at the end of the 19th century. At this point in time, the nationalistic reaction after the loss of the remaining colonies, supposes the abandon of a liberal regime, characterized by a relative openness, and the adoption of a nationalistic model of development that breaks the former dynamics and imposes harsh restrictions in the international trade of goods and raw materials. The paper pretends also to provide new evidence on the relationship between integration and industrial agglomeration in the presence of scale economies, by testing directly one of the predictions that can be derived from Krugman (1991) seminal paper, that is, the existence of regional nominal wage gradients and its transformation following changes in trade regimes. Hanson (1996, 1997, 1998) has analyzed in depth these effects in the case of the Mexican economy and has shown how trade reform has weakened the industrial belt around Mexico city, giving rise to new industrial centers in the north of the country. On the contrary, our case study analyzes the effects of the substitution of an open economy by a closed economy regime, exactly the opposite process studied by Hanson. To this aim, in the empirical analysis, we test the existence of a nominal wage gradient centered in Barcelona during the period 1914-1930. Our results indicate the existence of a wage gradient centered in Barcelona during the interwar period (1914-1930) and its weakening after 1925. The evidence on the genesis of a new wage gradient centered in Madrid is not conclusive.
Keywords: 330